Fatigue?oxidation interaction models for life prediction of hot-forming tools steels under transient thermomechanical loadings. (17th June 2008) - Daffos, C.; Lamesle, P.; Rezai-Aria, F.
This contribution deals with the life prediction of the virgin and nitrided hot-working tool steels X38CrMoV5 (AISI H11, 47 HRC) under Transient Thermomechanical (TMF) loading. Isothermal Low Cycle Fatigue (LCF) and thermomechanical (TMF) behaviour are investigated at different temperatures and various frequencies. It is shown that nitruration can enhance the fatigue life only when the strain amplitude is lower than a critical value. Two Manson-Coffin laws govern the fatigue life of the virgin and nitrided steels for all temperatures and strain rates investigated. However, these models have shortcomings for predicting TMF life. Predictive fatigue life models take into account the interaction with oxidation. Regarding the second tempering temperature (550?C) and the steel surface (virgin or nitrided), a Paris-type (T > 550?C) or a Tomkins-type (T < 550?C) law is used. A modified Tomkins model considering the mean residual stress measured by X-Ray at high temperature in the nitrided layer is used. The model is applied for isothermal and thermal mechanical fatigue experiments performed and reported in literature.